Design of Interactive Spaces for Promoting Parental Involvement: Strategies Used by EFL Teachers - Guo, Dongni; Ramos, Roberto; Zhao, Yingru; Sun, Qi (Online Learning, 2025)
This study investigated the strategies used by five Chinese EFL teachers in designing practices in utilization of digital tools and visuals for promoting parent-involved interactions in online language learning environments. Qualitative analysis of teacher interview transcripts, recorded videos, student artwork, and teacher–parent–student discourses on digital learning platforms and social media revealed six themes emerged regarding digital-screen-mediated design. The themes indicate that these designs such as using recorded videos to extend instructions and using assignment instructions to create collaborative meaning making environments, facilitates authentic communication and interactions among teachers, students, and parents. The mediation process extended beyond merely illustrating, sharing, or anchoring targeted visual content with parents and students; it also involved co-creation and co-construction of visuals on the screen. The emerging co-constructed learning structures aligned with five types of parent-involved interactive configurations. The findings of this study will assist EFL teachers to develop more effective instructional strategies in online or blended learning environments, particularly for young EFL learners.